Risk of stillbirth, preterm delivery, and fetal growth restriction following exposure in a previous birth: systematic review and meta‐analysis. (3rd October 2017) - Malacova, E; Regan, A; Nassar, N; Raynes‐Greenow, C; Leonard, H; Srinivasjois, R; W Shand, A; Lavin, T; Pereira, G
Abstract : Background: Little is known about the risk of non‐recurrent adverse birth outcomes. Objectives: To evaluate the risk of stillbirth, preterm birth (PTB), and small for gestational age (SGA) as a proxy for fetal growth restriction (FGR) following exposure to one or more of these factors in a previous birth. Search strategy: We searched MEDLINE, EMBASE, Maternity and Infant Care, and Global Health from inception to 30 November 2016. Selection criteria: Studies were included if they investigated the association between stillbirth, PTB, or SGA (as a proxy for FGR) in two subsequent births. Data collection and analysis: Meta‐analysis and pooled association presented as odds ratios (ORs) and adjusted odds ratios (aORs). Main results: Of the 3399 studies identified, 17 met the inclusion criteria. A PTB or SGA (as a proxy for FGR) infant increased the risk of subsequent stillbirth ((pooled OR 1.70; 95% confidence interval, 95% CI, 1.34–2.16) and (pooled OR 1.98; 95% CI 1.70–2.31), respectively). A combination of exposures, such as a preterm SGA (as a proxy for FGR) birth, doubled the risk of subsequent stillbirth (pooled OR 4.47; 95% CI 2.58–7.76). The risk of stillbirth also varied with prematurity, increasing three‐fold following PTB <34 weeks of gestation (pooled OR 2.98; 95% CI 2.05–4.34) and six‐fold following preterm SGA (as a proxy for FGR) <34 weeks of gestation (pooled OR 6.00; 95% CI 3.43–10.49). A previous stillbirth increased the risk of PTB (pooled OR 2.82; 95% CI 2.31–3.45), and subsequent SGA (as a proxy for FGR) (pooled OR 1.39; 95% CI 1.10–1.76). Conclusion: The risk of stillbirth, PTB, or SGA (as a proxy for FGR) was moderately elevated in women who previously experienced a single exposure, but increased between two‐ and three‐fold when two prior adverse outcomes were combined. Clinical guidelines should consider the inter‐relationship of stillbirth, PTB, and SGA, and that each condition is an independent risk factor for the other conditions. Tweetable abstract: Risk of adverse birth outcomes in next pregnancy increases with the combined number of previous adverse events. Plain Language Summary: Why and how was the study carried out?: Each year, around 2.6 million babies are stillborn, 15 million are born preterm (<37 weeks of gestation), and 32 million are born small for gestational age (less than tenth percentile for weight, smaller than usually expected for the relevant pregnancy stage). Being born preterm or small for gestational age can increase the chance of long‐term health problems. The effect of having a stillbirth, preterm birth, or small‐for‐gestational‐age infant in a previous pregnancy on future pregnancy health has not been summarised. We identified 3399 studies of outcomes of previous pregnancies, and 17 were summarised by our study. What were the main findings?: The outcome of the previous pregnancy influenced the risk of poor outcomes in the next pregnancy. Babies born to mothers who had a previous preterm birth or small‐for‐gestational‐age birth were more likely to be stillborn. The smaller and the more preterm the previous baby, the higher the risk of stillbirth in the following pregnancy. The risk of stillbirth in the following pregnancy was doubled if the previous baby was born both preterm and small for gestational age. Babies born to mothers who had a previous stillbirth were more likely to be preterm or small for gestational age. What are the limitations of the work?: We included a small number of studies, as there are not enough studies in this area (adverse birth outcomes followed by adverse cross outcomes in the next pregnancy). We found very few studies that compared the risk of small for gestational age after preterm birth or stillbirth. Definitions of stillbirth, preterm birth categories, and small for gestational age differed across studies. We did not know the cause of stillbirth for most studies. What are the implications for patients?: Women who have a history of poor pregnancy outcomes are at greater risk of poor outcomes in following pregnancies. Health providers should be aware of this risk when treating patients with a history of poor pregnancy outcomes. Abstract : Tweetable abstract Risk of adverse birth outcomes in next pregnancy increases with the combined number of previous adverse events.